Allah's best friend - Khan, Saniyasnain (New Dehli, Good word books, 2003)
The book narrates the story of Prophet Ibrahim (Abraham), highlighting his unwavering faith and devotion to Allah. It emphasizes the importance of recognizing and submitting to the one true God, Allah, and serves as an excellent resource for parents and educators aiming to instill Islamic values in young children through storytelling.